2021
DOI: 10.1186/s12876-021-01693-w
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota composition and functional prediction in diarrhea-predominant irritable bowel syndrome

Abstract: Background Irritable bowel syndrome (IBS) is common and difficult to treat and its pathogenesis is closely related to gut microbiota. However, differences in gut microbiota of patients in different regions make it more difficult to elucidate the mechanism of IBS. We performed an analysis of gut microbiota composition and functional prediction in Chinese patients with diarrhea-predominant IBS (IBS-D). Methods Fecal samples were obtained from 30 IBS-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
21
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 43 publications
8
21
0
4
Order By: Relevance
“…Moreover, it is noteworthy fecal (stool) and mucosal sampling is critical during the determination of the microbial dysbiosis in IBD ( Lo Presti et al, 2019 ). The IBD stool samples are characterized by reduced diversity of microbiota in comparison to IBS and healthy population ( Mei et al, 2021 ). IBD cases are characterized by decreased Verrucomicrobia and Bacteroidetes than healthy population ( Lo Presti et al, 2019 ; Mei et al, 2021 ).…”
Section: Gut Microbiota Dysbiosis In Ibdmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, it is noteworthy fecal (stool) and mucosal sampling is critical during the determination of the microbial dysbiosis in IBD ( Lo Presti et al, 2019 ). The IBD stool samples are characterized by reduced diversity of microbiota in comparison to IBS and healthy population ( Mei et al, 2021 ). IBD cases are characterized by decreased Verrucomicrobia and Bacteroidetes than healthy population ( Lo Presti et al, 2019 ; Mei et al, 2021 ).…”
Section: Gut Microbiota Dysbiosis In Ibdmentioning
confidence: 99%
“…The IBD stool samples are characterized by reduced diversity of microbiota in comparison to IBS and healthy population ( Mei et al, 2021 ). IBD cases are characterized by decreased Verrucomicrobia and Bacteroidetes than healthy population ( Lo Presti et al, 2019 ; Mei et al, 2021 ). On the other hand, in case of IBS Bacteroidetes are increased in comparison to healthy population.…”
Section: Gut Microbiota Dysbiosis In Ibdmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the article mentioned the increased number of bacteria belonging to Firmicutes phyla, including Lactobacillus and Ruminococcus genus, as well as a decreased abundance of Erysipelotrichaceae and methanogens in IBS patients [61]. Mei et al (2021), who analyzed only IBS-D patients in China, also observed elevated abundance of bacteria belonging to Enterobacteriaceae family, as well as Proteobacteria phyla, and decreased prevalence of Firmicutes, Fusobacteria phyla, and Alloprevotella, Fusobacterium genus in contrast to the healthy population [62]. Tap et al (2017) observed the correlation between the severity of IBS and the number of Methanobacteriales capable of producing methane, which is linked to the occurrence of constipation [63].…”
Section: Intestinal Microbiota In Patients With Irritable Bowel Syndromementioning
confidence: 99%